D-stem mutation in an essential tRNA increases translation speed at the cost of fidelity. - Madison N Schrock; Krishna Parsawar; Kelly T Hughes; Fabienne F V Chevance (PLoS Genetics)
The efficiency with which aminoacyl-tRNA and GTP-bound translation elongation factor EF-Tu recognizes the A-site codon of the ribosome is dependent on codons and tRNA species present in the polypeptide (P) and exit (E) codon sites. To understand how codon context affects the efficiency of codon recognition by tRNA-bound EF-Tu, a genetic system was developed to select for fast translation through slow-translating codon combinations. Selection for fast translation through the slow-translated UCA-UAC pair, flanked by histidine codons, resulted in the isolation of an A25G base substitution mutant in the D-stem of an essential tRNA LeuZ, which recognizes the UUA and UUG leucine codons. The LeuZ(A25G) substitution allowed for faster translation through all codon pairs tested that included the UCA codon. Insertion of leucine at the UCA serine codon was enhanced in the presence of LeuZ(A25G) tRNA. This work, taken in context with the Hirsh UGA nonsense suppressor G24A mutation in TrpT tRNA, provides genetic evidence that the post-GTP hydrolysis proofreading step by elongation factor Tu may be controlled by structural interactions in the hinge region of tRNA species. Our results support a model in which the tRNA bending component of the accommodation step in mRNA translation allows EF Tu time to enhance its ability to differentiate tRNA interactions between cognate and near-cognate mRNA codons.